2022
DOI: 10.1111/exd.14547
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptomics in human skin research: available technologies, technical considerations and disease applications

Abstract: The human skin is defined by a multilayer architecture based on diverse cell populations of mainly keratinocytes and fibroblasts, as well as various immune cells, melanocytes, adipocytes and endothelial cells that orchestrate events leading to wound repair of pathogenic infections and exposure to ultraviolet radiation and toxic compounds. 1 The transcriptomic profile of skin can provide information on gene expression, non-coding regulatory elements and gene splicing, and therefore shed light on skin physiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 107 publications
0
18
0
Order By: Relevance
“…These have been used successfully to decipher pathways of skin stromal cell development 11,12 and how wound healing across the life span is accompanied by an altered inflammatory milieu 13 . Alteration in skin landscape have similarly been studied in psoriaisis and atopic dermatitis 14 and cancer 15 , promising to contribute to the development of new therapeutic approaches to target these and other skin disorders. Skin-microbiota interactions have received much attention, with implications for normal homeostasis, immune system health and the response to infection 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…These have been used successfully to decipher pathways of skin stromal cell development 11,12 and how wound healing across the life span is accompanied by an altered inflammatory milieu 13 . Alteration in skin landscape have similarly been studied in psoriaisis and atopic dermatitis 14 and cancer 15 , promising to contribute to the development of new therapeutic approaches to target these and other skin disorders. Skin-microbiota interactions have received much attention, with implications for normal homeostasis, immune system health and the response to infection 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous bulk RNA sequencing and microarray studies on skin inflammatory diseases have revealed dysregulation of inflammatory and barrier genes, but many cell-specific transcripts often remain masked in whole-skin transcriptomic analyses. In addition, it has been difficult to systematically understand the sophisticated interplay among cells in the skin ( 3 ). Sing-cell RNA-seq (scRNA-seq) can capture tissue transcripts at the single-cell resolution and effectively solve this problem ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been difficult to systematically understand the sophisticated interplay among cells in the skin ( 3 ). Sing-cell RNA-seq (scRNA-seq) can capture tissue transcripts at the single-cell resolution and effectively solve this problem ( 3 ). The experimental procedure of scRNA-seq mainly includes four steps: sample preparation, cell enrichment, library preparation, and data analysis ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…including genomics [13], transcriptomics [14], metabolomics [15], microbiomics [16], and proteomics [17]. The effects of drugs on macaques have been explored using multi-omics analysis, greatly promoting biomedical research.…”
Section: Introductionmentioning
confidence: 99%